Lisocabtagene Maraleucel for Richter's Transformation—A Case Series - Courtney J. Smith; Anmol Goyal; Brian R. Smith; Dasom Lee; Alexandria Jensen; Jonathan Alexander; Melody Smith; Matthew Frank; Saurabh Dahiya; David Miklos; Sushma Bharadwaj (eJHaem)
ABSTRACT Introduction Richter's transformation (RT) from chronic lymphocytic leukemia (CLL) to lymphoma carries poor prognosis. This case series examines the efficacy of lisocabtagene maraleucel (liso‐cel) in six RT patients, highlighting the impact of concurrent ibrutinib therapy. Methods Six patients were with RT who received liso‐cel from were included in this single institution case series. Clinical data related to efficacy, safety, CAR‐T expansion kinetics, and measurable residual disease were collected. Results The best overall response was 83.3%. The four patients who received ibrutinib concurrent with liso‐cel therapy continue to show MRD‐negative complete response till date. None experienced severe (grade 3+) cytokine release syndrome while 1 had severe (grade 3+) immune‐effector cell‐associated neurotoxicity syndrome (ICANS). All patients were noted to have in vivo CAR expansion. Conclusion This series of real cases suggests liso‐cel with concurrent ibrutinib may be a promising treatment for RT, warranting further exploration.